Comparative Analysis of Mitragynine Content in Kratom Leaves (Mitragyna speciosa Korth) from Kabupaten Kapuas Hulu Using HPLC Method - Novianry, Virhan; Astuti, Puji; Andriani (Universitas Kristen Duta Wacana, 2024)
Opioid drugs are common analgesics for managing chronic pain, but they have significant short- and long-term side effects. Despite this, opioid consumption continues to rise in high-income countries, raising concerns about dependency. Kratom (Mitragyna speciosa Korth), which has opioid-like effects, shows potential as an analgesic with fewer side effects. This study aimed to explore and compare the mitragynine content in Kratom leaves from various regions in Kabupaten Kapuas Hulu, Indonesia, using High-Performance Liquid Chromatography (HPLC). Kratom leaves from 14 regions in Kapuas Hulu were collected, dried, and ground. Mitragynine was extracted using 70% ethanol and analyzed with HPLC. The yield percentage and mitragynine content in both the powdered simplisia and ethanol extract were measured and compared. The study showed that the average ethanol extract yield was 28%, with the highest yield from Elis Menendang (31.20%) and the lowest from Nanga Lauk (23.86%). Mitragynine content was significantly higher in the ethanol extract (3.22%) compared to the powdered simplisia (1.46%). Samples from Lanjak, Jongkong, Bunut, and Putussibau Kota showed mitragynine content exceeding 4% in the ethanol extract. HPLC analysis indicated that ethanol extraction significantly increases the mitragynine content in Kratom leaves compared to powdered simplisia, up to twice as much.